2018
DOI: 10.3389/fmicb.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide Array and VITEK Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry in Species Identification of Blood Yeast Isolates

Abstract: We evaluated matrix-assisted laser desorption ionization time-of-flight mass spectrometry using VITEK MS (IVD database) and an oligonucleotide array based on the internal transcribed spacer-1 (ITS-1) and ITS-2 sequences of rRNA genes for the identification of Candida spp. from blood cultures. Five-hundred and twelve consecutive bloodstream yeast isolates were collected daily and initially identified by the phenotypic automated method (VITEK YBC or VITEK2 YST card). Inconsistent results were confirmed by D1-D2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Analysis of these two articles revealed several factors that can explain the observed heterogeneity. We found that Li et al [23] mentioned that several isolates were identified as ‘bad spectrum during acquisition’ in the discussion of the article. We think this may affect the results of mass spectrometry to some extent.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Analysis of these two articles revealed several factors that can explain the observed heterogeneity. We found that Li et al [23] mentioned that several isolates were identified as ‘bad spectrum during acquisition’ in the discussion of the article. We think this may affect the results of mass spectrometry to some extent.…”
Section: Discussionmentioning
confidence: 89%
“…For example, C. guilliermond i (100%), C. krusei (100%), C. dubliniensis (100%), and so on. But there were a few exceptions, like C. dubliniensis (2/3) [23] and C. rugosa (6/7) [18]. Because of too few samples, in order to ensure scientific preciseness and avoid excessive heterogeneity, we cannot verify the accuracy of MALDI-TOF-MS in these rare Candida species.…”
Section: Discussionmentioning
confidence: 99%
“…This observation can be related to the lower patient flow through ICU, and less antibiotics used. More rapid and accurate MALDI-TOF diagnostics may help reduce the time of antibiotic exposure ( 13 ). It is expected that by reducing the total number of infections, the prevalence of Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search, study selection and collective expert evaluation will be repeated every 6 months. Denis et al (2018), Gaisne et al (2018), Li et al (2018), Mount et al (2018), Musatti et al (2018), Mixao and Gabaldon (2018), Robledo-Leal et al (2018), Rosenberg et al (2018), Scott et al (2018), Steenkamp et al (2018), Steenkamp et al (2018), Phadke et al (2018), Sivamaruthi (2018), Wayakanon et al (2018) Relevant to the QPS exercise…”
Section: B6mentioning
confidence: 99%